Mecanismos de acción de los principales herbicidas preemergentes utilizados en el cultivo de maíz (Zea mays) en el Ecuador - Ochoa García, Cecibel del Rocio (2025)
Corn (Zea mays) is one of the most important crops worldwide, being a fundamental pillar for the economy, due to its usefulness as food for humans and livestock, this crop is a source of a large number of industrial products. However, its production is constantly threatened by competition from weeds, which significantly reduce yields and grain quality, limiting crop productivity. In this sense, knowledge of the intervention of the mechanisms of action of pre-emergent herbicides plays an important role, since their application occurs before the germination of weeds, preventing their development and growth. Therefore, the objective of this study focuses on determining the mechanisms of action of the main pre-emergent herbicides used in corn (Zea mays) cultivation in Ecuador. To carry out this document, a meticulous collection of updated information was carried out, covering scientific articles, websites and virtual libraries. The most common pre-emergence herbicides were found to be those containing active ingredients such as atrazine, acetochlor, metolachlor and pendimethalin. It was concluded that the mechanisms of action of pre-emergence herbicides are based on the inhibition of processes essential for weed survival, such as cell division, photosynthesis and amino acid synthesis.